Can Digital Color Applications be an Alternative to Color Spectrophotometers? - Kizilkaya, Aye Rencber; Kara, Aybuke; Ipek, Irem (Quintessence Publishing Co Inc, 2026)
Purpose: To compare the digital colorimeter program (DCM), clinical spectrophotometer (SPM), and visual color measurement (3D-Master) used in determining the color of the restoration in vivo. Materials and Methods: Color analyses were performed using three different methods from the points determined on the maxillary right and left central incisors of 15 volunteers (n = 30). Color measurement analyses were performed using the Vita Easyshade V Device from three different points on each tooth. For visual assessments, the patient was instructed to select the color closest to their natural teeth using the Vita Toothguide 3D-Master color scale. Then a cross-polarized filter and a gray reference card were used with a camera, and intraoral photographs of the volunteers were taken. All images were transferred to the computer, the data processed with the Adobe Photoshop Lightroom software were transferred to the DCM, and color measurement analyses of the teeth were performed. The average color difference between these three methods was calculated with the CIEDE2000 (AE(00)) formula. One-way ANOVA and Bonferroni tests were applied to evaluate the data, and P values equal to or less than .05 were considered statistically significant. Results: When three different methods were compared for each tooth, no statistically significant difference was observed between the SPM and 3D-Master groups in a* coordinates or between the 3D-Master and DCM groups in b* coordinates, while a statistically significant difference was observed between all groups in L* coordinates and mean AE(00) (P < .001). Conclusions: Considering that the data may be affected by the limitations of the visual analysis method and the spectrophotometer, the digital analysis method, which provides quantitative data, is anticipated to assist clinicians in color measurement due to its practicality and repeatability.
Keywords: Accuracy